Analysis of Management Performance Ratio on Irrigation Water Distribution in Subak Gede Kedewatan - Suweta, I Made Bayu; Tika, I Wayan; Aviantara, I Gusti Ngurah Apriadi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The Management Performance Ratio (MPR) is a comparison between the water flowrate given and the water flowrate requirement for each agricultural land. The subak system in Bali is based on socio technical-religious and economic concepts. This study aims to calculate the MPR value and its distribution as well as find out the irrigation water distribution strategy so that irrigation performance becomes "adequate" to "good" in Subak Gede Kedewatan, Gianyar Regency. This research was carried out using a quantitative analysis approach through surveys and direct measurements in the field. The result showed that percentage distribution of MPR criteria for "good" was 5 subaks (18.52%), "adequate" 4 subaks (14.81%), "poor" 9 subaks (33.33%), and "very poor" 9 subaks (33 ,33%). The MPR value of subak in the upstream area is entirely in the "very poor" criterion with an MPR value of 1.85. Followed by subak in the central region, all of them are in the "low" criterion with an MPR value of 1.45. In contrast to the downstream, the subaks in this area have the criteria of "adequate" and "good" with a distribution of RPM values of 0.64 - 1.05. Subaks that get excess water, then the rest of the irrigation water is channeled to the pangkung, which will be the main water source for subak natak tiyis (tapping taps).